Climate Policy Enhances Efficiency: A Macroeconomic Portfolio Effect - Jan Siegmeier; Linus Mattauch; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2015)
Carbon pricing regulates emission flows and collects rents from underlying fossil resource stocks. The resulting investment shift implies lower climate policy costs and improved welfare if capital is underaccumulated. We prove that under emission trading, such a beneficial macroeconomic portfolio effect between fossil stocks and capital is induced if some permits are auctioned. Alternatively, a carbon tax also induces a portfolio effect, but cannot simultaneously implement a given mitigation path and collect an arbitrary rent share. Finally, treating the right to recurrently receive a share of total emission permits as a tradable asset is formally, but not politically equivalent.
Keywords: E22; H21; H23; Q30; Q54; 330; carbon pricing; resource rent taxation; overlapping generations; capital underaccumulation